Agricultural Short Message Services as Information for Farmer Empowerment - Djuara Lubis; Asri Sulistiawati (Jurnal Komunikasi Pembangunan, 2021)
Layanan Informasi Desa/Rural Information Service (LISA) is an information service for farmers based on SMS. It is used to disseminate agricultural information and provide a space for agricultural tips, ask questions and have a discussion. This study was conducted to determine the response and the perceived benefits of these services for farmer households. The study was conducted in Karawang, where LISA was launched. The results showed that the frequency of LISA’S use varied greatly from once per week to 30 times per week, but no farmer household used Android-based applications. The frequency of use of these services is significantly related to satisfaction level and is associated with the level of knowledge of farmer households. On the other hand, the frequency of use of LISA is unrelated to the characteristics of farmer households, which include age, education, sex, land ownership, as well as participation in farmer groups, and cosmopolitanism. A higher level of knowledge is also related to the suitability of the tips given by LISA and the degree of satisfaction with the LISA.